Quality Evaluation on The Implementation of Electronic Medical Records in Primary Health Centers - Rosita, Riska; Wisda Tumarta Arif, Yunita; Rohman Wachid, Naufal; Ristianingsih, Tsasa (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Primary Health Centers in Indonesia must implement Electronic Medical Records (EMR) through SIMPUS in accordance with PMK/24/2022 concerning Medical Records. Primary Health Center X has implemented EMR since September 2023. However, EMR often experiences downtime, which hampers the process of distributing medical records between health service units and patients must wait until the server returns to normal. This study aims to conduct an evaluation to determine the quality of EMR at Primary Health Center X. This type of research is a qualitative descriptive study with a cross-sectional approach. The population were all health workers in the outpatient service section at Primary Health Center X, with a sample taken using the total sampling technique of 19 respondents. Data analysis was carried out descriptively quantitatively on the EMR system using the PIECES method. The results of the EMR quality evaluation study based on the PIECES method show that the performance aspect is categorized as good (72.9%), the information aspect is categorized as very good (76.5%), the economy aspect is categorized as very good (79.3%), the control aspect is categorized as very good (75.1%), the efficiency aspect is categorized as very good (76.6%) and the service aspect is categorized as very good (76.0%). The conclusion of the calculation of the average percentage index of all aspects is that the EMR system is very good (76.06%).